2009
DOI: 10.1080/00223890802634274
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Theory-Driven Profile Interpretation of the Dutch Short Form of the MMPI Using the TAT Social Cognitions and Object Relations Scale (SCORS)

Abstract: In this study, we investigated the construct validity of the theory-driven profile interpretation of the Dutch Short Form of the MMPI (DSFM; Luteijn & Kok, 1985), an interpretation method aimed at assessing structural features of personality based on Kernberg and Caligor's (2005) views concerning personality organization. We utilized the four dimensions of the Social Cognition and Object Relations Scale (SCORS; Westen, Lohr, Silk, Gold, & Kerber, 1990) as external criteria. Results showed that, congruent with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
11
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 46 publications
3
11
0
2
Order By: Relevance
“…This is in agreement with the notion that the introversion/extraversion dimension is a temperamental disposition influencing the type of personality disorder (internalizing versus externalizing) but not the severity of structural personality pathology [39]. For a more detailed description of the rationale behind the assessment method, and the interpretation of the several DSFM profiles see [34,35].…”
Section: Introductionsupporting
confidence: 71%
See 2 more Smart Citations
“…This is in agreement with the notion that the introversion/extraversion dimension is a temperamental disposition influencing the type of personality disorder (internalizing versus externalizing) but not the severity of structural personality pathology [39]. For a more detailed description of the rationale behind the assessment method, and the interpretation of the several DSFM profiles see [34,35].…”
Section: Introductionsupporting
confidence: 71%
“…These groups are mutually exclusive. Several studies have provided evidence for the validity of the DSFM to capture features of PO [31,[34][35][36][37][38]. In the present study, internal consistency of the several subscales ranged from 0.69 (subscale Severe Psychopathology) to 0.90 (subscale Shyness).…”
Section: Methodsmentioning
confidence: 57%
See 1 more Smart Citation
“…Patients with good-to-moderate anxiety tolerance and who are overcontrolled are classified as having a neurotic PO. Within the borderline PO domain, Eurelings-Bontekoe et al (2009a) distinguish, in increasing order of severity of structural personality pathology, four subgroups that are characterized by having (a) moderate or good anxiety tolerance and, relative to their anxiety tolerance, moderate control (immature borderline PO); (b) good anxiety tolerance but undercontrol (narcissistic borderline PO); (c) poor anxiety tolerance and strong control, relative to their anxiety tolerance (high-level borderline PO); and (d) poor anxiety tolerance and undercontrol (low-level borderline PO). Finally, patients with PPO or psychotically vulnerable BPO have poor anxiety tolerance and weak control.…”
Section: Methodsmentioning
confidence: 99%
“…Recent research (Eurelings-Bontekoe & Luyten, 2010;Eurelings-Bontekoe et al, 2008;Eurelings-Bontekoe et al, 2009a, 2009bEurelings-Bontekoe, Luyten, IJssennagger, Van Vreeswijk, & Koelen, 2010a;Eurelings-Bontekoe, E. H. M., Luyten, P., Remijsen, M. & Koelen, 2010b;Eurelings-Bontekoe, Peen, Noteboom, Alkema, & Dekker, 2012) has provided support for the construct and predictive validity of this assessment model. Eurelings-Bontekoe et al (2012), in a naturalistic follow-up study of 2,062 outpatients, showed differential treatment responses of patients with various BPO profiles.…”
mentioning
confidence: 96%